Factors Affecting the Net Profit of Manufacturing Companies Listed on The Indonesia Stock Exchange - Hidayat, Imam; Aprilia Sari, Petty (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To test whether there is an influence of transformational leadership style, career development, and organizational culture on employee performance. Background Problems: The pharmaceutical industry is facing a moderately raised condition where the demand for pharmaceutical products related to handling Covid-19 is increasing, on the other hand the demand for products that are not directly related to Covid-19 has decreased. Novelty: Re-testing on the same variable by previous researchers, with the data analyzed and different research locations. Research Methods: The analysis used is multiple regression analysis which is preceded by a classic assumption test consisting of a normality test, multicollinearity test, autocorrelation test & heteroscedasticity test. Hypothesis testing was carried out using the t test and F test, using 36 observation data and analysis tools using SPSS. Finding/Results: The regression results show that production costs partially have no significant effect on net income, promotion costs partially have a significant effect on net income, and sales volume has a significant effect on net income. Conclusion: To reduce production costs to a minimum and avoid wasting costs related to production costs to maintain or increase profits